A pedagogical approach to the formulation of fingering options for selected piano works of Debussy, Scriabin, Rachmaninoff, Ravel, Bartók, and Prokofiev : a practice-led study - Stanford, Joseph (University of Pretoria, 2022)
Thesis (DMus (Performing Art))--University of Pretoria, 2021.